9, 9′‐Bifluorenylidene‐Core Perylene Diimide Acceptors for As‐Cast Non‐Fullerene Organic Solar Cells: The Isomeric Effect on Optoelectronic Properties. Issue 16 (19th February 2018) - Zhao, Yuan; Wang, Huan; Xia, Shengpeng; Zhou, Feng; Luo, Zhenghui; Luo, Jiajia; He, Feng; Yang, Chuluo
Abstract: Two different non‐fullerene small‐molecule acceptors, m ‐PIB and p ‐PIB, based on 9, 9′‐bifluorenylidene (BF) and perylene diimide (PDI) were designed and synthesized. Four β‐substituted PDIs were linked to BF in different positions. Based on DFT analysis, derivative p ‐PIB exhibited reduced intramolecular twisting between the PDI moieties, more delocalized wave function, and sufficiently wider π‐electron delocalization than that of m ‐PIB . The absorption ability of p ‐PIB was enhanced due to increased intermolecular interactions. By blending p ‐PIB with poly{4, 8‐bis[5‐(2ethylhexyl)thiophen‐2‐yl]benzo[1, 2‐ b :4, 5‐ b′ ]dithiophene‐ co ‐3‐fluorothieno[3, 4‐ b ]‐thiophene‐2‐carboxylate} (PTB7‐Th), organic solar cells (OSCs) based on p ‐PIB obtained a maximum power conversion efficiency of 5.95 % without any treatments. Due to the improved and balanced hole and electron mobilities, the short‐circuit current and fill factor of OSCs based on PTB7‐Th and p ‐PIB were significantly increased. The AFM and TEM results revealed that the PTB7‐Th: p ‐PIB film had favorable nanoscale phase separation and formed a bicontinuous interpenetrating network. Abstract : Core configuration : Isomeric effect on the optoelectronic properties of two small‐molecule non‐fullerene acceptors based on bifluorenylidene and perylene diimide were investigated. Organic solar cells based on these materials achieved the highest power conversion efficiency of 5.95 % without any treatments (see figure).